2019
DOI: 10.1002/ijgo.12791
|View full text |Cite
|
Sign up to set email alerts
|

Impact and cost of preoperative computed tomography imaging on the management of patients diagnosed with high‐grade endometrial cancer

Abstract: Objective To investigate the cost and impact of routine preoperative computed tomography (CT) in patients with high‐grade endometrial cancer, and its role in identifying extrauterine disease. Methods We retrospectively identified patients with high‐grade endometrial cancer who underwent routine CT scan prior to surgical procedure between September 1, 2005, and January 31, 2015. Cases in which CT findings led to alterations in the treatment plan were documented. Incidental findings unrelated to endometrial canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Besides, some studies have supported the significant flaws of CT, which were also found here. Few studies have recommended CT for MI assessment, but it is widely used to evaluate extrauterine lesions and lymph node enlargement [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, some studies have supported the significant flaws of CT, which were also found here. Few studies have recommended CT for MI assessment, but it is widely used to evaluate extrauterine lesions and lymph node enlargement [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies echoed significant CT flaws, consistent with our results. Few studies have recommended CT for myometrial invasion, widely used for extrauterine lesions and lymph node enlargement 25,26 …”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of maximal standardized uptake value in classifying patients into pre-defined riskgroups is limited [101]. A preoperative computed tomography (CT) scan has a clin- ical utility in patients with endometrial carcinoma in detecting metastatic disease [102,103]. Frozen section of endometrial biopsy material is obsolete.…”
Section: Pre-and Intra-operative Work-upmentioning
confidence: 99%